A highly potent and selective inhibitor Roxyl-WL targeting IDO1 promotes immune response against melanoma. (1st January 2018) - Xu, Guangwei; Wang, Tianqi; Li, Yongtao; Huang, Zhi; Wang, Xin; Zheng, Jianyu; Yang, Shengyong; Fan, Yan; Xiang, Rong
Abstract: Indoleamine 2, 3-dioxygenase 1 (IDO1) activity links to immune escape of cancers. Inhibition of IDO1 provides a new approach for cancer treatment. Most clinical IDO1 drugs show marginal efficacy as single agents. On basis of molecular docking and pharmacophore modelling, a novel inhibitor Roxyl-WL was discovered with a half maximal inhibitory concentration (IC50) value of 1 nM against IDO1 and 10–100-fold increased potent activity compared with IDO1 drugs in clinical trials. Roxyl-WL displayed excellent kinase spectrum selectivity with no activity out of the 337 protein kinases. In vitro, Roxyl-WL effectively augmented the proliferation of T cells and reduced the number of regulatory T cell (Tregs).When administered to melanoma (B16F10) tumor-bearing mice orally, Roxyl-WL significantly suppressed tumor growth and induced immune response.